Profile of elderly patients receiving antiretroviral therapy at Newlands Clinic in 2020: A cross-sectional study - Cleophas Chimbetete; Tinashe Mudzviti; Tinei Shamu (AOSIS, 2020)
Background: People living with HIV (PLWH) face new challenges such as accelerated ageing and higher rates of comorbidities including cardiovascular, renal and metabolic diseases as they age. Objectives: To profile the demographic and clinical characteristics of elderly patients receiving HIV care at Newlands Clinic (NC), Harare, Zimbabwe, as of 01 October 2019. Methods: A cross-sectional analysis was conducted using clinic data. All patients who were 50 years and older on 01 October 2019 were enrolled. Descriptive statistics (medians, interquartile ranges [IQRs] and proportions) were used to describe patient demographic and clinical characteristics. Results: Out of 6543 patients undergoing care at NC, 1688 (25.8%) were older than 50 years. The median duration of antiretroviral therapy (ART) was 10.9 years (IQR: 7.1-13). Over 90% of all patients had an HIV viral load below 50 copies/mL. Women were more likely than men to be overweight and obese (32% and 25% vs. 18% and 7%, respectively). Hypertension (41.2%), arthritis (19.9%) and chronic kidney disease (11.6%) were common comorbidities differently distributed based on sex. The most common malignancy diagnosed in women was cervical intra-epithelial neoplasia (68% of cancer burden in women) and Kaposi sarcoma was the leading malignancy in men (41% of cancer burden in men). Nearly 20% of patients had at least two chronic non-communicable comorbidities and 5.6% had at least three. Conclusion: A high burden of comorbidities was observed amongst HIV-positive elderly patients receiving ART. Age-appropriate monitoring protocols must be developed to ensure optimum quality of care for elderly HIV-positive individuals.